KINERJA AKSES JAMAK OFDM-CDMA - Sukiswo, Sukiswo; Zahra, Ajub Ajulian (Departemen Teknik Elektro, Universitas Diponegoro, 2009)
Problems in the current telecommunications system is how to send data with a very high speed but limited in the frequency allocation. One of the solution of this problems that is used a OFDM (Orthogonal Frequency Division Multiplexing) system which is a multicarrier communication scheme where the inter-frequency subcarriers orthogonal to each other and overlapping each other so it can save the frequency allocation. To serve more than one user, OFDM systems have combined with a CDMA multiple access technique.A simulation of the OFDM system created using Matlab by applying the CDMA system for the multiple access technique in the OFDM system and known as CDMA-OFDM. Combination of these two techniques will increase the speed of data transmission and it can serve many users at one time. This final project aims to determine the influence of the number of users in the system, the long PN code, the number of subcarrier and the value of Eb/No CDMA-OFDM system in Additive White Gaussian Noise (AWGN) transmission channel. The performance of the system was known from the value of Bit Error Rate (BER) at receiver.For PN code length variation 32, 64 and 128, the simulation CDMA-OFDM system with 32 users showed that the longer PN code is used, the system will show a better performance. It can be seen from the value of the BER system is decreases. ForÂ PN code length 32, the system will show the value of BER 0 in the level of Eb/No 9 dB. For PN code length 64, the system will show the value of BER 0 in the level of Eb/No 7 dB and for PN code length 128, the system will show the value of BER 0 in the level of Eb/No 3 dB.Â Keywords: CDMA, OFDM, PN code, subcarrier, multiuser.